Monitoring in Intelligent Electrical Power Networks (Smart Grid) - Maśnicki, R.; Lisowski, M. (Scientific Journal of Gdynia Maritime University, 2018)
With advances in various fields of electrical engineering, traditional power transmission and distribution grids are transformed into intelligent power grids. An integral part of a network with this configuration is the communication medium, which is the physical layer of the communication network, allowing for the exchange of diverse data within the network. Numerous applications designed for intelligent networks, such as enabling remote reads of power meters, mostly require a low data rate, for which sufficient conditions create narrowband communications. The article discusses the basic assumptions of intelligent power grids and indicates selected communication standards implemented in these networks. A significant issue related to their use was identified: crosstalk among network segments. The concept of solving this problem was presented and preliminary results of simulation tests were recalled.